2013
DOI: 10.2528/pierb12120201
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grazing Angle Target Detection and System Configuration of Mimo Radar

Abstract: Abstract-In this paper, we focus on target detection and system configuration optimization of Multiple-input Multiple-output (MIMO) radar in low-grazing angle, where the multipath effects are very abundant. The performance of detection can be improved via utilizing the multipath echoes. First, the reflection coefficient, considering the curved earth effect, is derived. Then, the general signal model for MIMO radar is introduced for low-grazing angle. Using the NeymanPearson sense, the detector of MIMO radar wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In rich multipath environments, time reversal technique combined with MIMO radar was used to improve the detection performance [16] while a space-time adaptive processing (STAP) method was developed to mitigate the multipath clutter [17,18]. In [19], the authors demonstrated that the detection performance could be significantly improved through multipath utilization with statistical MIMO radar. The detection performances of two kinds of generalized likelihood ratio test (GLRT) detectors with hybrid MIMO radar in low grazing angel were discussed in [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rich multipath environments, time reversal technique combined with MIMO radar was used to improve the detection performance [16] while a space-time adaptive processing (STAP) method was developed to mitigate the multipath clutter [17,18]. In [19], the authors demonstrated that the detection performance could be significantly improved through multipath utilization with statistical MIMO radar. The detection performances of two kinds of generalized likelihood ratio test (GLRT) detectors with hybrid MIMO radar in low grazing angel were discussed in [20].…”
Section: Introductionmentioning
confidence: 99%
“…The solutions of other variables (such as r 1 , h r ) are omitted for brevity, see [19,21] for more details. The complex reflection coefficient is calculated by [22] ρ = Γ (ν,h) DS (7) where Γ (ν,h) is vertical polarization or horizontal polarization reflection coefficient for a plane surface; D is the divergence factor due to a curved surface; S is root-mean-squared (RMS) specular scattering coefficient which represents the roughness of surface.…”
Section: Multipath Propagation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous methods, such as spatial smoothing techniques, proposed removing the coherency [13,14]. It had been demonstrated in [15] that the detection performance could be enhanced via multipath utilization with a statistical multiple-input multiple-output (MIMO) radar. The authors have further investigated a hybrid MIMO radar for detecting low grazing angle targets in multipath propagation scenarios [16].…”
Section: Introductionmentioning
confidence: 99%
“…MIMO radar is categorized into two classes: the statistical MIMO radar and colocated MIMO radar, depending on their antenna placement [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%